Optimal tuning of robust proportional integral derivative based on sliding mode controller for an AVR system - Abdallah, Lemita; Ines, Lemita; Sami, Kahla (Bulletin of Electrical Engineering and Informatics, 2025)
The primary objective of the automated voltage regulator (AVR) is to maintain the terminal voltage of the synchronous generator at the specified level with great precision in power production systems. Accurate voltage regulation improves the longevity of equipment intended for operation at the specified voltage within a power system network. This study presents a robust control of an AVR system utilizing proportional integral derivative (PID) control based on sliding mode techniques. The suggested control method is implemented by utilizing the particle swarm optimization (PSO) technique to tune the parameters of the proposed controller in the AVR system. A comparative performance analysis is conducted between the proposed controller, PID controller, and (PSO-fractional order proportional integral derivative (FOPID) controller. The comparison is derived using transient response characteristics and parameter uncertainty. The results reveal that the proposed PSO-PID-sliding mode control (SMC) controller has superior performance, characterized by rapid convergence, reduced overshoot, stability achievements in time domains, and robustness against parameter fluctuations. The proposed controller has markedly enhanced the performance of the AVR system and can be effectively implemented inside it.